The analysis of pricing principles at domestic industrial enterprises - I.M. Rjabchenko; V.V. Bozhkova (Marketing i Menedžment Innovacij, 2013)
The analysis of pricing principles at domestic industrial enterprisesTheoretical and methodological aspects of marketing pricing formation are investigated in the article. The aim of this research is systematization of marketing pricing principles and formation of corresponding offers concerning perfection of a domestic industrial enterprises pricing policy.The results of the analysis. The authors note that pricing principles are important element of pricing methodology which form basic positions, characteristics for all pricing system. The essence of such pricing principles as scientific substantiation of prices, target direction of prices, unity principle of pricing process, principle of continuous pricing process, interrelation between pricing policy and general enterprise strategy, principle of legality, planned character, proportionality, adequacy, principle of interdependence between types and forms of selling, flexibility principle is considered.The table of the resulted principles allows us to group them after the followings descriptions:general principles: planned character principle, principle of legality, principle of proportionality, principle of adequacy, principle of flexibility;main principles: principle of scientific prices substantiation, principle of prices target direction, unity principle of pricing process, principle of continuous pricing process;specific principles: principle of connection between pricing policy and general strategy of enterprise, principle of interrelation between types and forms of selling, principle connected with the features of products which will be distribute, principle connected with buyers quality maintenance;individual principles: principle connected with market structure, principle that applies to the choice of reaction type and market conditions change and so on.Conclusions and directions of further researches. Research of theoretical and methodological aspects of marketing pricing forming enables to systematize existent pricing principles. The analysed principles are the basis of pricing policy. Within marketing activity in the sphere of pricing it is necessary to adhere principles mentioned above. The results of this research can be used in further scientific developments which will be connected with principles of marketing pricing, in the process of pricing strategy forming and in practical activity of domestic industrial enterprises.